Expression of Arabidopsis FCS-Like Zinc finger genes is differentially regulated by sugars, cellular energy level, and abiotic stress - Jamsheer K, Muhammed; Laxmi, Ashverya (Frontiers in Plant Science, 2015)
Cellular energy status is an important regulator of plant growth, development, and stress mitigation. Environmental stresses ultimately lead to energy deficit in the cell which activates the SNF1-RELATED KINASE 1 (SnRK1) signaling cascade which eventually triggering a massive reprogramming of transcription to enable the plant to survive under low-energy conditions. The role of Arabidopsis thaliana FCS-Like Zinc finger (FLZ) gene family in energy and stress signaling is recently come to highlight after their interaction with kinase subunits of SnRK1 were identified. In a detailed expression analysis in different sugars, energy starvation, and replenishment series, we identified that the expression of most of the FLZ genes is differentially modulated by cellular energy level. It was found that FLZ gene family contains genes which are both positively and negatively regulated by energy deficit as well as energy-rich conditions. Genetic and pharmacological studies identified the role of HEXOKINASE 1- dependent and energy signaling pathways in the sugar-induced expression of FLZ genes. Further, these genes were also found to be highly responsive to different stresses as well as abscisic acid. In over-expression of kinase subunit of SnRK1, FLZ genes were found to be differentially regulated in accordance with their response towards energy fluctuation suggesting that these genes may work downstream to the established SnRK1 signaling under low-energy stress. Taken together, the present study provides a conceptual framework for further studies related to SnRK1-FLZ interaction in relation to sugar and energy signaling and stress response.